Events. Issue 146 (July 2016) - Unknown
Abstract : National Association of Corporate Directors (NACD) 2016 Global Board Leaders' Summit How Policy Governance® Boards Can Best Ensure Healthy Organizational Culture Getting to "One Voice" IPGA Consultants' Forum BoardSource Harvard Business School Haines Centre HolacracyOne National Coalition for Dialogue & Deliberation (NCDD) National Council for Voluntary Organisations (NCVO) International Association of Facilitators (IAF) Sociocracy/Dynamic Governance